Analisis Pentingnya Kode Etik Public Relation dalam Menjaga Citra Perusahaan - Effendy, Erwan; Saima Putri Hsb; Salsa Fadilah Siregar; Yuli Awanda Harahap; Endah Rananda Gita Br Purba; Muhammad Yasim Harahap (Da'watuna: Journal of Communication and Islamic Broadcasting, 2024)
Public Relations (PR) has a crucial role in a company's success. PR helps shape a company's positive image in the eyes of the public, maintain good relationships with customers and stakeholders, support marketing strategies, and maintain the company's reputation when facing a crisis. This research uses the Literature Review Study research method. By using this method, research will explore the concepts contained in the PR code of ethics, such as honesty, integrity and social responsibility. The literature review will provide an in-depth understanding of the ethical values ​​that are the basis for maintaining and building a positive company image. This research shows that Public Relations practitioners as one of the links between a company and its public certainly have guidelines that must be implemented. This guideline relates to the ethics and morals that a Public Relations practitioner must carry out in supporting his work. Public Relations Ethics is used as a guideline for professionalism and consideration for a Public Relations practitioner in acting and making decisions. A Public Relations practitioner certainly has duties and responsibilities that play an important role in the company's image.